Evidências empíricas das competências profissionais críticas do CIO brasileiro - Vreuls, Etienne Hubert (2009)
The primary objective of this work is to obtain a CIO¿s Critical Competencies model which could be applied to Brazilian CIO. This study was conducted by an explanatory research in a quantitative approach. Theoretical studies were done to understand CIO¿s environment, his identity, his career and organizational relationship. The analysis was based on six CIO¿s competencies models which describe how this professional could have a better performance. The intention of this approach was to provide a better understanding about the research problem. Then a meta-model was done as well as a survey. Once applied on Internet, the survey had 111 valid respondents, all Brazilian CIOs. To obtain the final model statistical factorial analysis was applied to the answers. Each identified factor in the model corresponds to a critical competency for Brazilian CIO. The model was submitted to hypotheses tests trying to establish what is the relation between each resultant factor and the time in the role for each respondent as well as his company size. This study has emerged a CIO critical competencies model to the Brazilian CIO, regarding his good performance.